Insight and Associated Factors among Patients with Schizophrenia in Mental Specialized Hospital, Ethiopia, 2018. (17th November 2019) - Tariku, Mandaras; Demilew, Demeke; Fanta, Tolesa; Mekonnen, Meskerem; Abebaw Angaw, Dessie
Abstract : Background . Insight is the degree of the patient's awareness and understanding of their attributions, feelings, behavior and disturbing symptoms. Majority of the patients with schizophrenia have poor insight and insight is an important prognostic indicator in schizophrenia to enhance treatment compliances and reducing the risks of clinical deterioration. The main objective of this study was to assess insight and its associated factors among patients with schizophrenia at mental specialized hospital in Ethiopia. Methods . Institutional based cross-sectional study was conducted from May to June 2018 Mental Specialized Hospital among 455 patients with schizophrenia. Insight was measured by an abridged version of Scale to assess unawareness of mental disorder. Positive and Negative Syndrome Scale, Calgary depressive scale, Oslo social support scale was used to identify factors associated with insight. Simple and multiple linear regression analysis were used to assess associated factors of insight in the participants. Results . The mean score of insight was 13.66 (95% CI 13.27, 14.04). Age at first onset of illness, duration of treatments, depressive symptoms were inversely associated with mean insight score; whereas unemployed, positive and negative syndrome, previous hospitalization, >=2 episodes were positively associated with mean insight score. Conclusion . Nearly half of the study participants were scored above the mean insight score so, the clinicians and psychotherapists should have to work together to improve insight among patients with schizophrenia.